Kulturowe uwarunkowania rozwoju przedsiębiorstw we współczesnej gospodarce - Karcz, Kornelia (Cultural Determinants of Companies' Development in Contemporary Economy, 2005)
Globalization, economic integration and internationalization of companies could be considered as crucial processes in contemporary economy. Companies operating in multicultural environment should implement the cultural determinants into the strategy development. The relations between the national cultures and the culture of organization as well as the selected methodological issues connected with the research of the cultural influences on market entities behavior are discussed in the paper. Identification, understanding, acceptation and utilization of cultural differences in the process of strategy formulation could create the possibility to achieve competitive advantage for "cultural sensitive" companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 143-153